Proposta de um guia de boas práticas para a gestão de resíduos da construção civil em municípios de pequeno e médio porte do estado do Ceará - Rodrigues, Janne Kelly Oliveira (2022)
The construction industry is considered one of the most important activities for the social and economic development of a society, however, this sector behaves as great generator of impacts to the environment, mainly those related to high waste generation and improper disposal. The management of these wastes is municipal competence, however, there is a great difficulty, especially for the municipalities small and medium-sized companies, in meeting the legal requirements, compromising the development efficient management of these wastes. In this way, this research proposed a guide to good practices for the management of Civil Construction Waste (RCC) to small and medium-sized companies, with the aim of contributing to the reduction of environmental impacts caused by the RCCs and provide foundations for the development of strategies for municipalities that seek to adapt their waste management. Diagnostics of the municipal management of the construction waste from the general survey of data in the municipalities of Ceará, based on the National Sanitation Information System (SNIS) and the Plans Regional Integrated Solid Waste Management (PRGIRS) in the State of Ceará, and a case study in small and medium-sized cities in the Sertão Centro-Sul region. In addition Furthermore, a bibliographic survey and documental research were carried out to identify good practices in the differentiated management of RCC, selecting some Brazilian cities that present significant and distinctive experiences. Based on the results obtained, it was It is possible to verify that the municipalities of Ceará still have an inefficient management of RCC, in which most do not have regulatory instruments, in addition to adopting a undifferentiated collection of these residues. There are initiatives to reuse the generated RCC, mainly on public roads, grounding of land and/or works and use in works public. However, with regard to the final disposal, it was found that the situation is critical, because, for the most part, they are disposed of in dumps. Based on the diagnoses, 12 strategies and 36 actions, aiming to guide the initial planning and implementation of RCC management in small and medium-sized municipalities in Ceará.